"Must try harder." Is effort and performance validity testing a necessary part of pediatric neuropsychological assessment?. Issue 2 (2nd April 2020) - Tonks, James; Whitfield, Charlotte Katie; Williams, W. Huw; Slater, Alan M.; Frampton, Ian J.
Abstract: Neuropsychological assessments results have significant implications for pediatric populations, based upon the assumption that the young person has adopted an effortful approach and has engaged in assessment. There is a commonly-accepted risk to assuming the validity of neuropsychological assessment results with adults, and, therefore, performance validity testing (PVT) has become a major topic of research and investigation and has become an accepted part of routine assessment. The same approach has not been adopted in assessment with children and a paucity of studies has focused on PVT in children. We review studies that demonstrate that children are equal to adults in their ability to use deception and that clinicians cannot detect false-effort without use of validity tests. We explore how frequently such tests are used and how well they work in assessment with children, and the limits, complexities, and constraints of adapting adult tests. We advocate that adequate performance validity testing is essential in order to maximize confidence in the results and we hypothesize that assessment with pediatric populations should take into account a range of influences, such as neuro-developmental factors associated with age of the child and suitability of proposed measures according to the evidence-base.